Unimproved source of drinking water and its associated factors: Multivariable analysis of Somalia Integrated Household Budget Survey (SIHBS 2022) - Omar Muhumed Maidhane; Omran Salih (PLoS ONE, 2025)
This study investigates the prevalence and factors associated with the use of unimproved drinking water sources in Somalia, a nation severely impacted by conflict, climate change, and a large nomadic population, thus hindering progress towards Sustainable Development Goal 6 (SDG 6). A cross-sectional analysis was conducted using data from 11,949 households from the 2022 Somalia Integrated Household Budget Survey (SIHBS). Logistic regression was employed to identify associations between unimproved water source usage and various individual and community-level factors. The results show significant geographical disparities, with region being a strong predictor. Surprisingly, urban households demonstrated a higher likelihood of using unimproved water sources compared to rural households (Adjusted Odds Ratio [AOR] = 2.067). At the household level, unimproved water use was more prevalent in households headed by divorced (AOR = 1.598) or never-married individuals (AOR = 1.262), and in those residing in permanent or semi-permanent housing (AOR = 1.385). Conversely, food-insecure households had lower odds of using unimproved water (AOR = 0.878). The use of unimproved drinking water in Somalia is shaped by a complex interaction of community and household factors. These findings highlight the urgent need for geographically targeted interventions that address regional inequalities, the specific challenges of urban water supply, and household vulnerabilities. Further research is recommended to explore the unexpected associations with urban living and food insecurity, informing context-specific strategies by Somali authorities and international partners to improve public health and accelerate progress towards SDG Target 6.1.